Tumour necrosis factor receptor-1 associated periodic syndrome (TRAPS)-related AA amyloidosis: a national case series and systematic review. (14th March 2021) - Delaleu, Jérémie; Deshayes, Samuel; Rodrigues, Francois; Savey, Lea; Rivière, Etienne; Silva, Nicolas Martin; Aouba, Achille; Amselem, Serge; Rabant, Marion; Grateau, Gilles; Giurgea, Irina; Georgin-Lavialle, Sophie
Abstract: Objectives: TNF receptor-1-associated periodic syndrome (TRAPS) is a rare autosomal dominant autoinflammatory disorder associated with mutations in the TNF receptor super family 1 A ( TNFRSF1A ) gene. AA amyloidosis (AA) is the most severe complication of TRAPS. To study the occurrence and prognosis of AA in TRAPS, we conducted a retrospective study of all French cases and a systematic literature review. Methods: This case series includes TRAPS patients followed by our centre from 2000 to 2020 presenting with histologically confirmed AA. We conducted a systematic literature review on the PubMed and EMBASE databases for articles published up to February 2021 following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines and using the keywords: amyloidoisis, amyloid, TNF receptor-associated periodic syndrome, TNF receptor-associated periodic syndrome, tumor necrosis factor receptor-associated periodic syndrome, TRAPS, TNFRSF1A, familial hibernian fever and hibernian familial fever. Results: A total of 41 TRAPS with AA were studied: three new patients and 38 cases from the literature. AA diagnosis preceded that of TRAPS in 96% of cases, and 17/36 (47%) required renal replacement therapy. Death occurred in 5/36 (14%) with a median follow-up of 23 months. Effect of biologics on AA were available for 21 regimens in 19 patients: 10 improved renal function, seven stabilized and four worsened. Four patients (36% of transplanted patients) relapse AA on kidney graft (only one under etanercept). Conclusion: TRAPS is revealed by AA in most cases. Therefore, clinical features of TRAPS should be screened for in AA patients. IL-1 antagonist can help to normalize inflammation and to preserve renal function.